The Piano Prelude n. 1 by Eunice Katunda “à maneira popular” (in a folkway) (Orfeu, 2017)
This article proposes an interpretative reflection on the Piano Prelude n.1 byEunice Katunda, the sole piece that wastranscripted, from a collection of thirtyPreludes which were recorded on tape bythe composer herself. It aims to raise interpretative hypothesis around the observation written down in the score by thecomposer herself, “à maneira popular”, “ina folkway’.
Keywords: Eunice Katunda; Prelude; Interpretation; Popular piano; Performance